2017
DOI: 10.1177/2047487317702519
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for sudden cardiac death in childhood hypertrophic cardiomyopathy: A systematic review and meta-analysis

Abstract: Results: Twenty five studies (3394 patients) met inclusion criteria. We identified four conventional major risk factors which were evaluated in at least 4 studies and found to be statistically associated with an increased risk of death in at least 2 studies: previous adverse cardiac event (pooled hazard ratio 5.4 (95% CI 3.67-7.95), p <0.001 ); non-sustained ventricular tachycardia (pooled hazard ratio 2.13 (95% CI 1.21-3.74), p=0.009); unexplained syncope (pooled hazard ratio 1.89 (95% CI 0.69-5.16), p=0.22);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 47 publications
(194 reference statements)
2
85
1
1
Order By: Relevance
“…Heart failure-related events were uncommon, consistent with previous studies. [1][2][3][4][5][6][7] Notably, only 42.0% of deaths actually occurred while patients were in the pediatric age range, and the event rate remained constantly high during the follow-up period, which ran well into adulthood. In total, about one-quarter of the events occurred when patients were older than 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure-related events were uncommon, consistent with previous studies. [1][2][3][4][5][6][7] Notably, only 42.0% of deaths actually occurred while patients were in the pediatric age range, and the event rate remained constantly high during the follow-up period, which ran well into adulthood. In total, about one-quarter of the events occurred when patients were older than 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an equal expected prevalence by sex, women are less represented than men in HCM cohorts, ranging from 45% to 22% [5][6][7][8] . Regardless of ethnicity, females are generally older, with more advanced disease at diagnosis and greater likelihood of heart failure progression compared to males 5,6,[8][9][10] ; furthermore, female sex could be a minor risk factor for cardiovascular death in childhood HCM 11 . Reasons for such discrepancies are still unknown, and may reflect sex-related differences in the pathophysiology of HCM, ultimately relevant to risk stratification and management 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2017 a systematic meta-analysis was conducted by Norrish et al (28) on 3,394 patients below 18 years from 25 studies, and four major risk factors have been identified including previous adverse cardiac event, non-sustained ventricular tachycardia, unexplained syncope and extreme left ventricular hypertrophy. Along with these major criteria, left atrial diameter has been pointed out as an additional important risk factor (28). More recently, Norrish et al (45) developed a novel risk prediction model for sudden cardiac death in HCM children through a retrospective, multicenter, longitudinal cohort study on 1,024 patients below 16 years and the most predictive variables included in the model were unexplained syncope, degree of hypertrophy, LA diameter and NSVT, while the maximal LVOT gradient appeared to be inversely related with SCD risk, a data that clearly needs further investigation.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%